The Usage of Biogas as a Renewable Energy and its Impact on Environment in Malaysia - Yaacob, Safar; Mazura Hj. Mohaiyadin, Norlaila; Samsuri, Alinda; Azilah Mohd Kasim, Noor (International Journal of Engineering and Technology, 2018)
Air degradation and energy insecurity are currently critical worldwide issues and to encounter these issues, new sources and development of renewable energy and its impact on the environment should be explored. The aim of this study is to analyse the feasibility of using biogas from a cow’s dung for energy production. This study adopted the experimental lab research at National Defence University of Malaysia using lab scale radiator to test the effect and effectiveness of biogas usage for the environment. Biogas contains 50–80% methane and 40–50% carbon dioxide and it can be potentially altered to 95% methane prior to the usage of biogas. On managing biogas for power and fuel, two scenarios were focused: 1) impact to the environment and 2) impact on sewage water quality. This study contributes to the resource analysis of the biogas derived from cow’s dung, the economics of biogas production and biogas renewable energy policy in order to promote the green and healthy environment.